Determination of natural radioactivity concentrations and risk assessment in soil from mining sites in Minna environs, Niger State, Nigeria - Muhammad, A.; Abbasi, A. (Springer, 2025)
This research investigated the concentrations of the well-known naturally occurring radionuclide materials (NORMs) K-40, Ra-226, and Th-232 in soil samples obtained from three mining areas (Shakwata, Eregi, and Pina) from Niger State, Nigeria. The results showed low activity concentrations of NORMs in soil except K-40, which is above the world average. From the perspective of safety and considering the low level of radiation hazard indices, these samples can be considered safe for use in building and construction without causing radiological risk to the people residing in these areas.
Keywords: Activity concentrations; K-40; Ra-226 and Th-232; Gamma spectrometry; Radiological risk